New data on jumping spiders of Iran, with a new species of Salticus (Araneae: Salticidae) - Alireza Zamani; Marzieh Sadat Hosseini; Majid Moradmand (Arachnologische Gesellschaft eV, 2022)
On the basis of recently collected specimens in various regions of Iran, new data on jumping spiders (Salticidae) of this country are provided. One species, Salticus lucasi sp. nov. (♂, Isfahan Province, central Iran) is described as new to science, and three species (Chalcoscirtus platnicki Marusik, 1995, Mogrus larisae Logunov, 1995 and Phlegra yaelae Prószyński, 1998) are recorded in Iran for the first time. A further 21 species represent new provincial records.